Mulch with sugarcane bagasse and bamboo straw attenuates salt stress in cowpea cultivation - Inácio J. Barbosa; Henderson C. Sousa; Fernanda Schneider; Geocleber G. de Sousa; Carla I. N. Lessa; Lamine Sanó (Revista Brasileira de Engenharia Agrícola e Ambiental)
HIGHLIGHTS Saline stress did not affect the initial growth of the cowpea crop. The use of mulch provides better morphological results in the cowpea crop. Vegetal mulches as soil protection (sugarcane bagasse and bamboo straw) attenuated effect of salts on gas exchange of cowpea.